2021
DOI: 10.3389/fgene.2021.692702
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics and Metabolomics Reveal Purine and Phenylpropanoid Metabolism Response to Drought Stress in Dendrobium sinense, an Endemic Orchid Species in Hainan Island

Abstract: Drought stress is a bottleneck factor for plant growth and development, especially in epiphytic orchids that absorb moisture mainly from the air. Recent studies have suggested that there are complex transcriptional regulatory networks related to drought stress in Dendrobium sinense. In this study, the transcription and metabolite alterations involved in drought stress response in D. sinense were investigated through RNA-seq and metabolomics. A total of 856 metabolites were identified from stressed and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…Response of plants to water-deficient conditions can be observed at transcriptomic and metabolomic levels (Figure 2) [21,86,118]. You et al [21] studied drought-tolerant (DT) and drought-susceptible (DS) sesame genotypes under drought stress and found that DS plants were more disturbed by stress conditions that was confirmed at both transcriptional and metabolic levels.…”
Section: Transcriptomic and Metabolomic Changes In Plants Under Drought Stressmentioning
confidence: 96%
See 1 more Smart Citation
“…Response of plants to water-deficient conditions can be observed at transcriptomic and metabolomic levels (Figure 2) [21,86,118]. You et al [21] studied drought-tolerant (DT) and drought-susceptible (DS) sesame genotypes under drought stress and found that DS plants were more disturbed by stress conditions that was confirmed at both transcriptional and metabolic levels.…”
Section: Transcriptomic and Metabolomic Changes In Plants Under Drought Stressmentioning
confidence: 96%
“…In addition, other genes encoding for chaperones, including heat shock proteins (HSP) and small heat shock proteins (sHSP), Dna J proteins, aquaporins, orthologs of ABFs (ABA-Responsive-Element binding factors), and DREB2s (Dehydration-Responsive-Element-Binding Proteins 2), glutaredoxins (GRXs), glutathione S-transferase (GST), and many more can also be involved in plant response to drought stress [127][128][129][130][131][132][133][134][135][136]. Transcriptome analysis of the many other plants or crops such as pine (Pinus massoniana) [137], tea oil camellia (Camellia oleifera) [138], maize (Zea mays L.) [139], peanut (Arachis hypogaea L. varieties) [140], endemic orchid species (Dendrobium sinense) [118] under drought stress also provided insights into the molecular mechanism such as expression of drought stress genes and certain functional genes that helps the plant to cope with drought stress. Tahmasebi et al [141] investigated the transcriptional response of two different plant species (Oryza sativa (rice, C 3 plant) and Zea mays (maize, C 4 plant)) to drought stress based on 172 arrays in total from 11 drought stress studies.…”
Section: Transcriptomic and Metabolomic Changes In Plants Under Drought Stressmentioning
confidence: 99%
“…With the advent of high-throughput sequencing technologies, it has become increasingly feasible to explore a single gene or gene family [ 1 , 13 , 22 ]. To identify the key type III PKS genes involved in bibenzyl biosynthesis, the roots, pseudobulbs, and leaves of D. sinense were individually sequenced by Illumina platform.…”
Section: Discussionmentioning
confidence: 99%
“…The gene functions were annotated based on the public databases, as described in our previous study [ 1 ]. Bowtie software was used to compare the clean reads with unigene database.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation